ASSESSMENT AND MANAGEMENT OF THE FINANCIAL POTENTIAL OF TOURISM AND HOSPITALITY ENTERPRISES - VASYLIEVA, Tetiana; HRYTSENKO, Larysa; KOZHUSHKO, Irina; HAPONENKO, Svitlana; KUTSENKO, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The most optimal multi-component algorithm for assessing and managing the level of financial potential has been developed based on the analysis of the integral indicator, which is an aggregate indicator of the financial condition, liquidity, solvency, profitability and competitiveness of enterprise under the existing market conditions. During the analysis and study of the financial potential of tourism and hospitality enterprises, it is determined that it is advisable to divide the concept into financial potential of sustainability and financial potential of development, and it is found that the latter is significantly influenced by direct and indirect environmental factors. In view of this, the most significant factors influencing the level of financial potential of an enterprise in the process of realization of its strategic goals and prospective development opportunities have been analyzed and identified. In addition, a list of possible measures aimed at increasing the level of financial potential of tourism and hospitality enterprises has been developed. It has been established that the financial potential of enterprises in the field of tourism and hospitality is one of the key factors that characterize entrepreneurial activity in accordance with the available financial resources, financial condition and competitive market positions of the subject of economic relations, as well as development opportunities and promising areas of activity in conditions of dynamic and unstable economic environment. The value is in the formation of a methodology for assessing the level of financial potential and developing possible actions to improve it. Further research is proposed to be carried out in the context of developing scientific and methodological provisions for optimizing the structure of the financial potential of tourism enterprises in the process of implementing strategic goals of functioning, as well as the prospects for applying GAP analysis to identify and decompose internal strategic gaps by the constituent elements of financial potential.
Keywords: financial potential; the field of tourism and hospitality; assessment; integral indicator; management; competitiveness; financial resources; efficiency